Self-Concept of Homosexual Men Related to The Prevention of Risky Sexual Behavior in Kupang City - Fransiskus Yanto Seran; Yuliana Radja Riwu (Media Kesehatan Masyarakat, 2022)
A poor self-concept in homosexual men may increase the risk of transmission of sexually transmitted diseases, including HIV and AIDS. The purpose of the study was to describe the gay self-concept based on the aspects of knowledge, hope, and assessment. This research was qualitative with a phenomenological approach. The research informants were four gay men selected by using purposive sampling. The results showed that, based on the knowledge aspect, the informants acknowledged that homosexual behavior is a life choice influenced by genetic factors, environmental factors, and personal factors. The informants also admitted that they had been attracted to the same sex since childhood. Based on the aspect of hope, each informant has the hope of being accepted by the community while maintaining homosexual behavior, being able to marry the same sex, devoting himself to many people, especially homosexuals. Based on the assessment aspect, the informants feel proud and confident to be homosexual because they have unique talents that are different from heterosexual men. Suggestions related to this research are the need for socialization regarding the use of condoms, as well as the causes of homosexual behavior so that people do not isolate homosexuals but can guide and direct homosexuals to avoid deviant behavior such as always changing partners. In addition, it is necessary to check for sexually transmitted infections, especially in homosexual groups to prevent the transmission of HIV/AIDS.